Genetic analysis of wild Ancherythroculter nigrocauda in tributaries and the main stream of the upper Yangtze River basin of China. (2nd January 2020) - Yan, Taiming; Wang, Xiongyan; Li, Song; He, Zhide; Luo, Jie; Zhang, Qian; Yang, Deying; He, Zhi
Abstract: Biodiversity is threatened by several factors that are often associated with overfishing, water pollution and hydroelectric dams, among other environmental impacts. The present study aimed to evaluate the genetic aspects of wild groups of Ancherythroculter nigrocauda using the mitochondrial cytochrome c oxidase subunit I ( coI ) and cytochrome b ( cytb ) genes and the d-loop region. We collected 89 representative individuals from three geographically distinct ranges of the Upper Yangtze River, including the Longxi River (LOR), Laixi River (LAR), and Hejiang range of the Yangtze River (HJ). The genetic analysis results showed that the three populations of A. nigrocauda had high levels of haplotype diversity (0.3434–0.951) and low levels of nucleotide diversity (0.00074–0.00412) based on the single gene sequences and the combination of gene sequences. Haplotype genealogy showed that only one haplotype (Hap-2) was shared by these three geographic groups, and 2–3 were shared by two groups; the other haplotypes were group-specific. The genetic distance within and between the populations was low; however, most of the molecular variance came from within the populations. Furthermore, high gene flow (>1.0) was found in HJ vs LOR and HJ vs LAR based on the d-loop region sequence and combination. These results suggested that there was a decrease in the degree of A. nigrocauda genetic diversity in the upper Yangtze River, and the genetic protection of the populations should be highlighted in the future.